Instrumental measurements, as a basis for the automation of technological processes in the construction and operation of buildings and structures - Hrigorovsky, P. (Ways to Improve Construction Efficiency, 2019)
Methods of technology, mechanization and automation of technological processes, organization and project management are interrelated and are aimed at achieving a common goal - reducing the time and quality of construction, increasing the duration of the life cycle of construction projects through organizational and technological and technical solutions for the automatic management of technological processes using building information models and technologies, information obtained by methods of instrumental measurements at all groin of this cycle. The development of integrated models and methods for the automated system for diagnosing the technical condition of buildings is the initial stage in creating an integrated system for ensuring the operational suitability of buildings. The structure of the automated system integrates elements from instrumental measurements and data processing. Therefore, measurements, is the basis of the automation of technological processes at all stages of the life cycle depth.